Mineral Equilibrium Constraints on the Feasibility of Diffusively-Fluxed Melting in the Continental Crust - Tafur, Lorena Andrea (Department of Geological Sciences, 2020)
Generation of granitic magma predominantly occurs by melting through the breakdown of hydrous minerals. However, melting due to the influx of water has been recognised in anatectic amphibolite-facies composite grey gneisses, metagreywackes and low-pressure metapelites, and has consequently been proposed as an alternative mechanism for granite generation and crustal differentiation. Water-fluxed melting is recognised by voluminous melt production at relatively low temperature, where hydrous minerals are stable and anhydrous minerals are preferentially consumed during melting. Mineral equilibrium modelling to determine the P–T conditions, melt volumes, melting reactions and viable fluid sources reveal that water-present melting in all target lithologies is confined to the wet solidus and does not extend to temperatures higher than 700–710 ◦C. Melting at suprasolidus conditions does not involve the mechanical flow of a free water phase. Instead, the process is driven by diffusion of H2O along chemical potential gradients and is therefore more appropriately described as diffusively-fluxed melting. Diffusively-fluxed melting is not restricted to specific compositions or P–T conditions, although it is more efficient at lower pressure and in lithologies with a low hydrous mineral content. Melting reactions in all lithologies primarily consume quartz and feldspars to yield 5–6 mol.% melt for each mol.% of H2O added. aH2O remains constant at ∼0.70–0.77 during progressive melting as long as alkali feldspar is present. Once alkali feldspar is exhausted, plagioclase becomes the main reagent, producing more tonalitic melt compositions with gradually higher aH2O. Melting will initiate and proceed as long as a µH2O gradient exists between the fluid source and target lithology. Our calculations show that an ordinary magma, such as an I-type magma with typical, undersaturated H2O content, has a µH2O high enough to be a viable fluid source, allowing diffusively-fluxed melting to produce melt volumes and fertility comparable to that of dehydration melting. However, voluminous melt production requires a considerable volume of H2O, which necessitates a focussed fluid source such as a magma conduit or melt-bearing shear zone. Any other magmatic fluid source will undergo a similar amount of crystallisation as the melt fraction produced in the target rock, such that there will be no net melt production. Considering that shear-zone hosted magma conduits are relatively rare, diffusively-fluxed melting appears to only be viable in a small fraction of the anatectic orogenic crust. Therefore, whereas it may play a significant role in locally raising melt volumes and modifying magma chemistry through mingling and hybridisation, it does not appear to, of itself, be able to meaningfully contribute to crustal differentiation.